Nurse-led family-based approach in primary health care for patients with type 2 diabetes mellitus: a qualitative study - Khadija A. Matrook; Seamus Cowman; Maria Pertl; David Whitford (International Journal of Qualitative Studies on Health & Well-Being, 2024)
Purpose The prevalence of Type 2 diabetes is rapidly increasing, with 537 million people estimated to have diabetes in 2021. The literature suggests that nurses can deliver effective person-centred diabetes care and that families can be essential in supporting patients. Thus, a Nurse-led Family-based (NLFB) approach may be particularly effective. This study aims to explore the perceptions of nurses, adults with type 2 diabetes, and family members regarding the NLFB intervention. Methods Guided by the UK Medical Research Council Framework, this seminal study adopted a qualitative, descriptive approach with content analysis. Data were obtained through 16 semi-structured, in-depth interviews. Themes emerged based on an inductive process using constant comparison (Graneheim and Lundman 2004). The COREQ checklist was used in ensuring rigour. Results Three main themes emerged includes: (1) nurses’ experiences with current diabetes care practices, (2) stakeholders’ views on the development of a NLFB approach, and (3) merging the nurse-led family aspects into the diabetes care. The key challenges are the dominant medical model, lack of specialist nurses, and time. The key facilitators are knowledge and social support. Conclusion The study recommends stakeholders embrace nursing empowerment strategies and involve families to enhance the nurses’ advanced roles and family inclusion in healthcare.